Clinical predictors for ankle sprain recurrence of amateur volleyball athletes - David Costa Mendes; Mariene Cristine Silva Oliveira; Filipe de Souza Santos; Vanessa Eduarda Lopes Santos; João Warley Alves; Frederico Sander Mansur Machado; Rodolpho Cesar dos Reis Tinini; Ana Carolina de Mello Alves Rodrigues (Revista Brasileira de Ciências do Esporte)
ABSTRACT To evaluate the risk factors and complications in the recurrence of ankle sprains in amateur volleyball athletes. 22 male amateur volleyball athletes, divided into groups with sprains (n=11) and a control (n=11) were evaluated using the Foot and Ankle Outcome Score questionnaire, Visual Analogue Scale (VAS), Y Balance Test, Dorsiflexion Lunge. Our results indicate a direct correlation between the middle blocker and ankle sprains. A significant difference was observed between the groups on the VAS. The present study shows that reduced ankle range of motion, pain, athlete position are possible predictors for the recurrence of ankle sprains.